Bacteria Source Tracking Shapes a Holistic Watershed Management Plan. Issue 5 (1st May 2015) - Rogers, Peter D.; Walker, Laura; Fu, George; Frischer, Marc
Abstract : In 2005, several tidal water bodies near Savannah, Ga., were found to violate state fecal coliform and dissolved oxygen regulations. When the city and nearby stakeholders drew up a holistic watershed management plan, bacterial source tracking and fluorometry enabled them to target pollution reduction efforts.